Interface reinforcing material for well cementation and preparation method thereof

By using an interface reinforcement material composed of styrene-based monomers and other interfaces during the cementing process, the problems of oil-based drilling fluid retention and oil film formation are solved, and higher oil absorption effect and interface cementing strength are achieved, and cementing quality is improved.

CN119529200AActive Publication Date: 2025-02-28CHINA NAT PETROLEUM CORP +2

Patent Information

Application Number
CN202311090987.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28
Estimated Expiration
2043-08-28

AI Technical Summary

Technical Problem

Oil-based drilling fluid is prone to retention and form an oil film during cementing, affecting the fluidity and thickening performance of the cement ring and reducing the cementing quality.

Method used

An interface reinforcement material for cementing is adopted, which consists of styrene-based monomers, acrylate monomers, graphene oxide, organosiloxane, anionic monomers, cationic monomers, large steric resist crosslinkers and photoinitiators. It is prepared by a segmented photoinitiation polymerization process to form a composite gel network structure.

Benefits of technology

By modifying the specific surface area and hydrophobic oil-bearing properties of graphene oxide, this material realizes selective adsorption of oil phases in water, improves oil absorption effect and interface cementing strength, reduces the probability of oil and gas water traversing, and improves cementing quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention provides an interface reinforcing material for well cementation and a preparation method thereof. The interface reinforcing material for well cementation is prepared from the following components in parts by weight: 100 parts of styryl monomers, 30-50 parts of acrylate monomers, 5-10 parts of graphene oxide, 3-5 parts of organosiloxane, 3-5 parts of anionic monomers, 3-5 parts of cationic monomers, 3-5 parts of a large-steric-hindrance cross-linking agent, 0.5-1.5 parts of a photoinitiator and 200-300 parts of deionized water. Through re-crosslinking among the macromolecular microspheres, the oil absorption network volume and the oil product adsorption rate can be effectively improved, and the oil absorption effect is improved; due to the excellent specific surface area and hydrophobic and oleophylic characteristics of the modified graphene oxide, selective adsorption of an oil phase in water can be realized, and the influence of the material on a cement hydration process is reduced; the stability of the polymerization reaction and the dispersing performance of the material in cement paste are improved by introducing anion and cation monomers, and meanwhile, the toughness of the material and set cement is improved by virtue of the synergistic effect of ionic bonds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield cementing, and in particular to an interface reinforcement material for cementing and a preparation method thereof. Background Art

[0002] In the process of cementing oil and gas wells, the bonding quality between cement ring and casing and well wall is an important factor affecting the final cementing quality. Good interface bonding can improve the interlayer sealing effect of cementing, prevent the occurrence of oil-water crossflow, and ensure the productivity and life of oil and gas wells. In recent years, oil-based drilling fluid has been widely used in complex deep wells and unconventional horizontal wells such as mudstone, shale, salt-gypsum layer due to its good lubricity, inhibition, and pollution resistance. However, it is easy to stay in narrow annulus and irregular well diameter during construction, and often forms oil film on the well wall and casing surface. When mixed with cement slurry, it will affect the fluidity and thickening performance of cement slurry, and greatly reduce the body strength of cement stone after curing and the bonding quality of the first and second interfaces, affecting the integrity of cement ring and interlayer sealing ability, and seriously endangering the cementing quality.

[0003] In order to solve the problem of poor cementing quality at the cementing interface caused by oil-based drilling fluid contamination, the main treatment method at present is to develop efficient oil-washing pre-fluids, which effectively adsorb and remove the oil phase on the interface with lipophilic surfactants. On this basis, pre-fluid systems such as microemulsions and nanoemulsions have been developed one after another, and current research is also mainly focused on pre-fluids. However, due to the influence of factors such as contact time, wellbore conditions, temperature, and drilling fluid composition, it is often difficult to completely remove oil-based drilling fluids from the perspective of pre-fluids alone. Summary of the invention

[0004] In view of this, the present invention proposes an interface reinforcement material for cementing and a preparation method thereof, aiming to solve the above-mentioned technical problems existing in the prior art.

[0005] The first aspect of the present invention provides an interface reinforcement material for cementing, comprising the following components in parts by weight: 100 parts by weight of a styrene-based monomer, 30 to 50 parts by weight of an acrylate monomer, 5 to 10 parts by weight of graphene oxide, 3 to 5 parts by weight of an organic siloxane, 3 to 5 parts by weight of an anionic monomer, 3 to 5 parts by weight of a cationic monomer, 3 to 5 parts by weight of a large steric hindrance crosslinking agent, 0.5 to 1.5 parts by weight of a photoinitiator, and 200 to 300 parts by weight of deionized water.

[0006] Furthermore, in the above-mentioned interface reinforcement material for cementing, the styrene-based monomer is styrene, methyl styrene or tert-butyl styrene.

[0007] Furthermore, in the above-mentioned interface reinforcement material for cementing, the acrylic ester monomer is methyl acrylate, butyl acrylate, octadecyl acrylate, dodecyl methacrylate or isooctyl methacrylate.

[0008] Furthermore, in the above-mentioned interface strengthening material for cementing, the organosiloxane is vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane or γ-(methacryloyloxy)propyltrimethoxysilane.

[0009] Furthermore, in the above-mentioned interface reinforcement material for cementing, the anionic monomer is 2-acrylamide-2-methylpropane sulfonate, sodium p-styrene sulfonate or 2-methacryloyloxyethane sulfonate.

[0010] Furthermore, in the above-mentioned interface strengthening material for cementing, the cationic monomer is diallyldimethylammonium chloride, diallyldiethylammonium chloride or (3-acrylamidopropyl)trimethylammonium chloride.

[0011] Furthermore, in the above-mentioned interface enhancement material for cementing, the large steric hindrance cross-linking agent is ethylene glycol dicyclopentenyl ether acrylate, ethylene glycol dicyclopentenyl ether methacrylate or pentaerythritol triacrylate.

[0012] Furthermore, in the above-mentioned interface enhancement material for cementing, the photoinitiator is benzoin dimethyl ether, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide or 2,2-diethoxyacetophenone.

[0013] The first aspect of the present invention provides an interface enhancement material for cementing, which uses amphiphilic macromolecular microspheres as the rigid skeleton of the composite gel, and together with the introduced graphene oxide, gives the material good mechanical properties; the re-crosslinking between the macromolecular microspheres can effectively increase the oil absorption network volume and the oil adsorption rate, thereby improving the oil absorption effect; the excellent specific surface area and hydrophobic and lipophilic properties of the modified graphene oxide can achieve selective adsorption of the oil phase in water, reducing the influence of the material on the cement hydration process; the introduction of anionic and cationic monomers improves the stability of the polymerization reaction and the dispersion performance of the material in the cement slurry, and the synergistic effect of ionic bonds helps to improve the toughness of the material and cement paste.

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned interface reinforcement material for cementing, comprising the following steps:

[0015] A proper amount of organic siloxane is uniformly dispersed in anhydrous ethanol to obtain a siloxane solution, graphene oxide is dispersed in the siloxane solution, stirred at a preset temperature for a period of time, centrifuged, washed, separated again, and dried to obtain modified graphene oxide;

[0016] Take 0.5-1.5 parts of photoinitiator and evenly disperse it in 5-15 parts of deionized water to obtain an initiator solution;

[0017] According to the weight proportion of each component, styrene-based monomer, acrylate monomer, anionic monomer, cationic monomer, large steric crosslinking agent, photoinitiator solution and deionized water are added to a reaction kettle under light-proof conditions, and after stirring and dissolving, ultraviolet light is used to initiate the first preset time in a nitrogen atmosphere to obtain a macromolecular microsphere aqueous solution; after the temperature is cooled to room temperature, modified graphene oxide is added to the above-mentioned macromolecular microsphere aqueous solution, and after stirring and mixing, ultraviolet light is continuously used to initiate the second preset time in a nitrogen atmosphere to obtain a composite polymer hydrogel, which is dried, crushed and sieved to obtain an interface reinforcement material for cementing.

[0018] Furthermore, in the above-mentioned method for preparing the interface enhancement material for cementing, the first preset time length is 0.5-3 hours; the second preset time length is 0.5-2 hours.

[0019] The second aspect of the present invention provides a method for preparing an interface reinforcement material for cementing, which adopts a segmented light-initiated polymerization process. The cross-linking degree of the macromolecular microspheres themselves and the composite gel network formed by them can be accurately controlled by the light-initiated time, thereby achieving balanced regulation of the mechanical properties and oil absorption effect of the material, while having the advantages of low energy consumption and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic flow chart of a method for preparing an interface reinforcement material for cementing according to an embodiment of the present invention;

[0021] Figure 2A This is the SEM image of the interface after the separation of the clean slurry cement stone and the core;

[0022] Figure 2B This is a SEM image of the interface between the cement stone mixed with the interface reinforcement material for cementing in Example 5 of the present invention and the core after separation. DETAILED DESCRIPTION

[0023] The following is a preferred embodiment of the present invention. It should be noted that a person skilled in the art may make several improvements and modifications without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

[0024] The invention provides an interface reinforcement material for cementing, comprising the following components in parts by weight: 100 parts of styrene-based monomers, 30 to 50 parts of acrylate monomers, 5 to 10 parts of graphene oxide, 3 to 5 parts of organic siloxane, 3 to 5 parts of anionic monomers, 3 to 5 parts of cationic monomers, 3 to 5 parts of large steric hindrance crosslinking agents, 0.5 to 1.5 parts of photoinitiators and 200 to 300 parts of deionized water.

[0025] Specifically, the styrene-based monomer is styrene, methyl styrene or tert-butyl styrene. The styrene-based monomer mainly acts as a rigid group to give the material better mechanical properties.

[0026] The acrylic acid ester monomer is methyl acrylate, butyl acrylate, octadecyl acrylate, dodecyl methacrylate or isooctyl methacrylate. The acrylic acid ester monomer gives the material molecular chain flexibility and selectively adsorbs the oil phase according to the principle of like dissolves like.

[0027] The graphene oxide is commercially available graphene oxide powder with a flake diameter of 0.2 to 10 μm and a thickness of 0.5 to 1.2 nm.

[0028] The organosiloxane is vinyl trimethoxysilane, vinyl triethoxysilane, allyl trimethoxysilane, vinyl tri (β-methoxyethoxy) silane or γ- (methacryloyloxy) propyl trimethoxy silane.

[0029] The anionic monomer is 2-acrylamide-2-methylpropane sulfonate, sodium p-styrene sulfonate or 2-methacryloyloxyethane sulfonate.

[0030] The cationic monomer is diallyldimethylammonium chloride, diallyldiethylammonium chloride or (3-acrylamidopropyl)trimethylammonium chloride.

[0031] In this embodiment, ionic bonds can be formed between the anionic and cationic monomers to form new cross-linking sites in the system, which can improve the mechanical strength of the material and have a toughening effect.

[0032] The large steric hindrance crosslinking agent is ethylene glycol dicyclopentenyl ether acrylate, ethylene glycol dicyclopentenyl ether methacrylate or pentaerythritol triacrylate. In this embodiment, the large steric hindrance crosslinking agent is selected because its large steric hindrance can expose the residual double bonds after the first initiation to the outside of the macromolecular microspheres, which serve as new crosslinking points, and further polymerize with the introduced modified graphene oxide to finally form a composite polymer gel network structure.

[0033] The photoinitiator is benzoin dimethyl ether, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide or 2,2-diethoxyacetophenone.

[0034] The interface reinforcement material for cementing prepared by the present invention comprises the following steps: firstly, styrene-based monomers, acrylate monomers, anionic monomers and cationic monomers are copolymerized to form amphiphilic macromolecular microspheres with a three-dimensional network structure, and the amphiphilic macromolecular microspheres are used as the rigid skeleton of the composite gel, and together with the introduced graphene oxide, the material is endowed with good mechanical properties; the re-crosslinking between the macromolecular microspheres can effectively increase the oil absorption network volume and the oil adsorption rate, thereby improving the oil absorption effect; the excellent specific surface area and hydrophobic and lipophilic properties of the modified graphene oxide can realize the selective adsorption of the oil phase in water, thereby reducing the influence of the material on the cement hydration process; the hydrophilic groups are introduced through the anionic and cationic monomers, so that the particles have hydrophilic properties, which is beneficial to stabilizing the polymer emulsion particles, improving the emulsion stability, and improving the redispersibility of the polymer powder in the cement slurry, and the synergistic effect of the ionic bonds is helpful to improve the toughness of the material and the cement paste.

[0035] The present invention also provides a method for preparing an interface reinforcement material for cementing, comprising the following steps:

[0036] Step 1, uniformly dispersing an appropriate amount of organic siloxane in anhydrous ethanol to obtain a siloxane solution, dispersing graphene oxide in the siloxane solution, stirring at a preset temperature for a period of time, centrifuging, washing, separating again, and drying to obtain modified graphene oxide.

[0037] Specifically, 15-25 g of siloxane can be put into 1 L of ethanol solution, and graphene oxide can be dispersed in the siloxane solution by ultrasound, and the preset temperature is 40-80° C., preferably 60° C. The stirring time can be 4-10 hours, preferably 5 hours. In specific implementation, the siloxane solution of graphene oxide can be washed with deionized water for multiple times and then separated for the second time, and dried in a blast drying oven after the second centrifugal separation.

[0038] Step 2: Take 0.5 to 1.5 parts of photoinitiator and evenly disperse it in 5 to 15 parts of deionized water to obtain an initiator solution.

[0039] Step 3, according to the weight proportion of each component, add styrene-based monomers, acrylate monomers, anionic monomers, cationic monomers, large steric crosslinking agents, photoinitiator solution and deionized water into the reaction kettle under light-proof conditions, stir to dissolve, and then use ultraviolet light to initiate the first preset time in a nitrogen atmosphere to obtain a macromolecular microsphere aqueous solution; after the temperature is cooled to room temperature, add modified graphene oxide to the above-mentioned macromolecular microsphere aqueous solution, stir and mix, and then continue to use ultraviolet light to initiate the second preset time in a nitrogen atmosphere to obtain a composite polymer hydrogel, which is dried, crushed and sieved to obtain an interface reinforcement material for cementing.

[0040] Specifically, nitrogen bubbling can be used to stir and dissolve. In this embodiment, an aqueous solution of macromolecular microspheres is prepared by irradiation with an ultraviolet high-pressure mercury lamp under a nitrogen atmosphere. The photoinitiator decomposes into free radicals under ultraviolet light, thereby initiating polymerization and cross-linking of monomers to form macromolecular microspheres.

[0041] Since the photoinitiation time determines the degree of crosslinking of the polymer gel network, the degree of crosslinking increases with the reaction until it reaches equilibrium within a certain period of time. The mechanical properties of the material will increase with the increase in the degree of crosslinking, but the oil absorption and swelling capacity will decrease. Therefore, it is necessary to select a suitable time node during the polymerization process to ensure that the degree of crosslinking of the macromolecular microspheres and the composite gel network is controlled within a certain range, so that the material can take into account both good mechanical strength and oil absorption effects. Too long polymerization time will cause a certain degree of degradation of the polymer, affecting the performance of the product. Therefore, in this embodiment, the first preset time is 0.5-3h, preferably 1h; the second preset time is 0.5-2h, preferably 0.5h.

[0042] Since too large a particle size will affect the mechanical strength of cement paste, and too small a particle size will lead to poor ash dispersal in cement slurry, the dried and crushed composite polymer hydrogel can be screened using a vibrating screen with a screening particle size of 40-100 meshes, preferably, a vibrating screen with a screening particle size of 80 meshes is used.

[0043] It should be noted that, in practice, the order of step 1 and step 2 is not critical.

[0044] The preparation method of the interface reinforcement material for cementing provided by the present invention adopts a segmented light-initiated polymerization process, which can accurately control the cross-linking degree of the macromolecular microspheres themselves and the composite gel network formed by them through the light initiation time, thereby achieving balanced regulation of the mechanical properties and oil absorption effect of the material, and at the same time has the advantages of low energy consumption and high efficiency.

[0045] The present invention is described in detail below with reference to several embodiments.

[0046] Example 1

[0047] (1) Modification of graphene oxide: 15 g of allyltrimethoxysilane was uniformly dispersed in 1 L of anhydrous ethanol to obtain a siloxane solution. Graphene oxide was ultrasonically dispersed in the siloxane solution, stirred at 60°C for 5 h, centrifuged, washed with deionized water for multiple times, and dried in a forced air drying oven after centrifugation;

[0048] (2) Preparation of initiator solution: 2.5 g of benzoin dimethyl ether was uniformly dispersed in 50 g of deionized water to obtain an initiator solution;

[0049] (3) According to the weight proportion of each component, 500 g of styrene, 150 g of methyl acrylate, 15 g of 2-acrylamide-2-methylpropane sulfonate, 15 g of diallyldimethylammonium chloride, 15 g of ethylene glycol dicyclopentenyl ether acrylate, 950 g of deionized water and an initiator solution were added to a reaction kettle under light-shielding conditions, and nitrogen was bubbling and stirred to dissolve, and then irradiated with an ultraviolet high-pressure mercury lamp for 1 h under a nitrogen atmosphere to obtain a macromolecular microsphere aqueous solution. After the temperature was cooled to room temperature, 25 g of modified graphene oxide was added, and after stirring and mixing, ultraviolet initiation was continued for 0.5 h under a nitrogen atmosphere to obtain a composite polymer hydrogel, which was dried and crushed and passed through an 80-mesh vibrating sieve to obtain the interface reinforcement material for cementing.

[0050] Example 2

[0051] (1) Modification of graphene oxide: 25 g of vinyl tri(β-methoxyethoxy)silane was uniformly dispersed in 1 L of anhydrous ethanol to obtain a siloxane solution. Graphene oxide was ultrasonically dispersed in the siloxane solution, stirred at 60° C. for 5 h, and then centrifuged, washed with deionized water for multiple times, and dried in a forced air drying oven after centrifugation.

[0052] (2) Preparation of initiator solution: 7.5 g of benzoin dimethyl ether was uniformly dispersed in 50 g of deionized water to obtain an initiator solution.

[0053] (3) According to the weight proportion of each component, 500 g of methyl styrene, 250 g of butyl acrylate, 25 g of sodium p-styrene sulfonate, 25 g of diallyl diethyl ammonium chloride, 25 g of ethylene glycol dicyclopentenyl ether methacrylate, 1450 g of deionized water and an initiator solution were added to a reaction kettle under light-proof conditions, and nitrogen was bubbling and stirred to dissolve, and then irradiated with an ultraviolet high-pressure mercury lamp for 1 h in a nitrogen atmosphere to obtain a macromolecular microsphere aqueous solution. After the temperature was cooled to room temperature, 50 g of modified graphene oxide was added, and after stirring and mixing, ultraviolet initiation was continued for 1 h in a nitrogen atmosphere to obtain a composite polymer hydrogel, which was dried and crushed and passed through an 80-mesh vibrating sieve to obtain the interface reinforcement material for cementing.

[0054] Example 3

[0055] (1) Modification of graphene oxide: 20 g of vinyl trimethoxysilane was uniformly dispersed in 1 L of anhydrous ethanol to obtain a siloxane solution. Graphene oxide was ultrasonically dispersed in the siloxane solution, stirred at 60° C. for 5 h, and then centrifuged, washed with deionized water for multiple times, and dried in a forced air drying oven after centrifugation.

[0056] (2) Preparation of initiator solution: 6 g of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide was uniformly dispersed in 50 g of deionized water to obtain an initiator solution.

[0057] (3) According to the weight proportion of each component, 500 g of tert-butylstyrene, 170 g of octadecyl acrylate, 18 g of 2-methacryloyloxyethanesulfonate, 22 g of (3-acrylamidopropyl) trimethylammonium chloride, 18 g of pentaerythritol triacrylate, 1250 g of deionized water and an initiator solution were added to a reaction kettle under light-shielding conditions, and nitrogen was bubbling and stirred to dissolve. The mixture was irradiated with an ultraviolet high-pressure mercury lamp for 1.5 h under a nitrogen atmosphere to obtain a macromolecular microsphere aqueous solution. After the temperature was cooled to room temperature, 30 g of modified graphene oxide was added, and the mixture was stirred and mixed. The mixture was then ultraviolet-induced for 1 h under a nitrogen atmosphere to obtain a composite polymer hydrogel. The composite polymer hydrogel was dried and crushed through an 80-mesh vibrating sieve to obtain the interface reinforcement material for cementing.

[0058] Example 4

[0059] (1) Modification of graphene oxide: 25 g of vinyl triethoxysilane was uniformly dispersed in 1 L of anhydrous ethanol to obtain a siloxane solution. Graphene oxide was ultrasonically dispersed in the siloxane solution, stirred at 60° C. for 5 h, and then centrifuged, washed with deionized water for multiple times, and dried in a forced air drying oven after centrifugation.

[0060] (2) Preparation of initiator solution: 3 g of benzoin dimethyl ether was uniformly dispersed in 50 g of deionized water to obtain an initiator solution.

[0061] (3) According to the weight proportion of each component, 500 g of methyl styrene, 200 g of dodecyl methacrylate, 24 g of sodium p-styrene sulfonate, 16 g of diallyl diethyl ammonium chloride, 22 g of ethylene glycol dicyclopentenyl ether methacrylate, 1150 g of deionized water and an initiator solution were added to a reaction kettle under light-proof conditions, and nitrogen was bubbling and stirring to dissolve, and then irradiated with an ultraviolet high-pressure mercury lamp for 1 h in a nitrogen atmosphere to obtain a macromolecular microsphere aqueous solution. After the temperature was cooled to room temperature, 40 g of modified graphene oxide was added, and after stirring and mixing, ultraviolet initiation was continued for 1 h in a nitrogen atmosphere to obtain a composite polymer hydrogel, which was dried and crushed through an 80-mesh vibrating sieve to obtain the interface reinforcement material for cementing.

[0062] Example 5

[0063] (1) Modification of graphene oxide: 20 g of γ-(methacryloyloxy)propyltrimethoxysilane was uniformly dispersed in 1 L of anhydrous ethanol to obtain a siloxane solution. Graphene oxide was ultrasonically dispersed in the siloxane solution, stirred at 60° C. for 5 h, and then centrifuged, washed with deionized water for multiple times, and dried in a forced air drying oven after centrifugation.

[0064] (2) Preparation of initiator solution: 5 g of 2,2-diethoxyacetophenone was uniformly dispersed in 50 g of deionized water to obtain an initiator solution.

[0065] (3) According to the weight proportion of each component, 500 g of styrene, 200 g of isooctyl methacrylate, 20 g of 2-acrylamide-2-methylpropane sulfonate, 20 g of (3-acrylamidepropyl) trimethylammonium chloride, 20 g of ethylene glycol dicyclopentenyl ether acrylate, 1200 g of deionized water and an initiator solution were added to a reaction kettle under light-shielding conditions, and nitrogen was bubbling and stirred to dissolve. Then, the mixture was irradiated with an ultraviolet high-pressure mercury lamp for 1 h under a nitrogen atmosphere to obtain a macromolecular microsphere aqueous solution. After the temperature was cooled to room temperature, 35 g of modified graphene oxide was added, and after stirring and mixing, ultraviolet initiation was continued for 0.5 h under a nitrogen atmosphere to obtain a composite polymer hydrogel. After drying and grinding, the mixture was passed through an 80-mesh vibrating sieve to obtain the interface reinforcement material for cementing.

[0066] Comparative Example

[0067] The specific steps of the photoinitiated polymerization are as follows: according to the weight proportions of each component, 500g of styrene, 150g of methyl acrylate, 15g of 2-acrylamide-2-methylpropane sulfonate, 15g of diallyldimethylammonium chloride, 25g of modified graphene oxide, 15g of ethylene glycol dicyclopentenyl ether acrylate, 950g of deionized water and an initiator solution are added to a reactor under light-proof conditions, nitrogen is bubbling and stirring to dissolve, and then irradiated with an ultraviolet high-pressure mercury lamp for 1.5h under a nitrogen atmosphere to obtain a polymer hydrogel, which is dried and crushed through an 80-mesh vibrating sieve to obtain the interface reinforcement material for cementing. Other than this, the rest is the same as Example 1.

[0068] Experimental Example 1

[0069] The interface reinforcement materials for cementing of the embodiments and comparative examples were tested for oil absorption performance. A certain mass of dried interface reinforcement materials (m1) was placed in a non-woven bag, immersed in diesel or white oil at room temperature (25°C), taken out every 30 minutes, hung for 5 minutes until the surface oil phase drained away, and weighed. When the mass (m2) no longer changed, the measurement was stopped to obtain the saturated oil absorption rate (Q) of the polymer. The results are shown in Table 1, and the calculation formula is shown in Formula (1):

[0070] Q=(m2-m1) / m1×100% (1)

[0071] Table 1 Test results of oil absorption performance of different samples

[0072]

[0073]

[0074] It can be seen from Table 1 that the saturated oil absorption rates of Examples 1 to 5 provided by the present invention are significantly higher than those of the comparative examples. This is because the composite gel network formed by segmented photoinitiated polymerization provides more oil phase adsorption sites and has a better adsorption and swelling effect on the oil-based drilling fluid.

[0075] Experimental Example 2

[0076] Cement slurry was prepared according to GB / T 19139-2012 standard, and the interface bonding strength performance test was carried out.

[0077] Cement slurry formula 1: Jiahua G-grade oil well cement 100g + cementing interface reinforcement material 3g + fluid loss reducer BXF-200L (AF) 4g + retarder BXR-200L 0.2g + fresh water 41g + defoaming agent G603 0.5g.

[0078] Cement slurry formula 2: Jiahua G-grade oil well cement 100g + fluid loss reducer BXF-200L (AF) 4g + retarder BXR-200L 0.2g + fresh water 41g + defoaming agent G603 0.5g.

[0079] Take a Φ25mm×50mm shale core, soak it in oil-based drilling fluid for 1 hour, then take it out and let it stand. When the surface oil-based drilling fluid flows away and the core weight no longer changes, place the core in a test steel casing, add cement slurry in the annular space between the core and the steel casing, and cure it under normal pressure and 80℃ water bath conditions. After curing to the specified age, use a compressive strength tester to push out the core to obtain the interface shear bonding strength value. The schematic diagram is shown in the figure. Figure 1 , the results are shown in Table 2.

[0080] Table 2 Test results of cement paste interface bonding strength performance

[0081]

[0082] As can be seen from Table 2, the addition of the interface reinforcement material for cementing prepared by the present invention can significantly improve the interface bonding quality between the cement sheath and the well wall under the oil-based drilling fluid, and the interface bonding strength can be increased by 3 to 5 times compared with the neat slurry cement stone, ensuring that the cement slurry can still have a certain sealing strength when invaded by oil, which provides a strong guarantee for the cementing quality under complex well conditions.

[0083] FIG2(A) and FIG2(B) are scanning electron microscope images of the interface between the above-mentioned neat cement paste and the cement paste mixed with interface reinforcing material (Example 5) after separation from the core, respectively. It can be seen that the hydration process of the neat cement paste slows down after encountering oil, and the structure formed at the interface is loose and porous, with more amorphous CSH (calcium silicate hydrate) gel; while the structure formed at the interface after the interface reinforcing material is mixed is dense and uniform, which can effectively improve the interface sealing ability and improve the cementing quality.

[0084] Experimental Example 3

[0085] Cement slurry was prepared according to GB / T 19139-2012 standard, cured under normal pressure and 80°C water bath conditions, and the compressive strength of cement paste was tested.

[0086] Cement slurry formula 1: Jiahua G-grade oil well cement 100g + cementing interface reinforcement material 3g + fluid loss reducer BXF-200L (AF) 4g + retarder BXR-200L 0.2g + fresh water 41g + defoaming agent G603 0.5g.

[0087] Cement slurry formula 2: Jiahua G-grade oil well cement 100g + fluid loss reducer BXF-200L (AF) 4g + retarder BXR-200L 0.2g + fresh water 41g + defoaming agent G603 0.5g.

[0088] Table 3 Cement stone compressive strength test results

[0089]

[0090] As shown in Table 3, the addition of the interface reinforcement material for cementing prepared by the present invention will reduce the compressive strength of cement paste to a certain extent, but this effect can be reduced by adjusting the ratio of styrene-based monomers and acrylate monomers in the macromolecular microspheres, the amount of crosslinking agent used, and the ultraviolet initiation time. In the ratio of styrene-based monomers and acrylate monomers, the increase in the proportion of the former will increase the polymer rigidity and reduce its influence on the mechanical properties of cement paste. At the same time, the increase in the amount of crosslinking agent and the increase in ultraviolet initiation time will increase the crosslinking degree of the system, thereby improving the mechanical strength of the material, so that the cement slurry can still meet the requirements of cementing construction while taking into account the oil absorption performance, and achieve a balance between oil invasion resistance and mechanical properties (that is, the compressive strength of cement paste can be appropriately sacrificed under the condition of significantly improving the interface bonding strength, but it is necessary to ensure that the construction requirements are met).

[0091] In summary, the interface enhancement material for cementing prepared by the present invention is a new type of cement slurry admixture. When the residual oil-based drilling fluid on the interface is difficult to be replaced and cleaned by the pre-fluid, it can effectively adsorb and disperse the oil phase, improve the interface bonding strength between the cement ring and the casing and the well wall, reduce the probability of oil, gas and water channeling, and improve the quality of cementing. The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as a limitation on the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present invention, several deformations and improvements can be made, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. An interface reinforcement material for cementing, characterized in that: The invention comprises the following components in parts by weight: 100 parts of styrene-based monomers, 30 to 50 parts of acrylic acid ester monomers, 5 to 10 parts of graphene oxide, 3 to 5 parts of organic siloxane, 3 to 5 parts of anionic monomers, 3 to 5 parts of cationic monomers, 3 to 5 parts of large steric hindrance crosslinking agents, 0.5 to 1.5 parts of photoinitiators and 200 to 300 parts of deionized water.

2. The interface reinforcement material for cementing according to claim 1, characterized in that: The styrene-based monomer is styrene, methyl styrene or tert-butyl styrene.

3. The interface reinforcement material for cementing according to claim 1, characterized in that: The acrylic acid ester monomer is methyl acrylate, butyl acrylate, octadecyl acrylate, dodecyl methacrylate or isooctyl methacrylate.

4. The cementing interface reinforcement material according to claim 1, characterized in that: The organosiloxane is vinyl trimethoxysilane, vinyl triethoxysilane, allyl trimethoxysilane, vinyl tri (β-methoxyethoxy) silane or γ- (methacryloyloxy) propyl trimethoxy silane.

5. The interface reinforcement material for cementing according to claim 1, characterized in that: The anionic monomer is 2-acrylamide-2-methylpropane sulfonate, sodium p-styrene sulfonate or 2-methacryloyloxyethane sulfonate.

6. The interface reinforcement material for cementing according to claim 1, characterized in that: The cationic monomer is diallyldimethylammonium chloride, diallyldiethylammonium chloride or (3-acrylamidopropyl)trimethylammonium chloride.

7. The interface reinforcement material for cementing according to claim 1, characterized in that: The large steric hindrance crosslinking agent is ethylene glycol dicyclopentenyl ether acrylate, ethylene glycol dicyclopentenyl ether methacrylate or pentaerythritol triacrylate.

8. The interface reinforcement material for cementing according to claim 1, characterized in that: The photoinitiator is benzoin dimethyl ether, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide or 2,2-diethoxyacetophenone.

9. A method for preparing an interface reinforcement material for cementing as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: A proper amount of organic siloxane is uniformly dispersed in anhydrous ethanol to obtain a siloxane solution, graphene oxide is dispersed in the siloxane solution, stirred at a preset temperature for a period of time, centrifuged, washed, separated again, and dried to obtain modified graphene oxide; Take 0.5-1.5 parts of photoinitiator and evenly disperse it in 5-15 parts of deionized water to obtain an initiator solution; According to the weight proportion of each component, styrene-based monomer, acrylate monomer, anionic monomer, cationic monomer, large steric crosslinking agent, photoinitiator solution and deionized water are added to a reaction kettle under light-proof conditions, and after stirring and dissolving, ultraviolet light is used to initiate the first preset time in a nitrogen atmosphere to obtain a macromolecular microsphere aqueous solution; after the temperature is cooled to room temperature, modified graphene oxide is added to the above-mentioned macromolecular microsphere aqueous solution, and after stirring and mixing, ultraviolet light is continuously used to initiate the second preset time in a nitrogen atmosphere to obtain a composite polymer hydrogel, which is dried, crushed and sieved to obtain an interface reinforcement material for cementing.

10. The method for preparing an interface reinforcement material for cementing according to claim 9, characterized in that: The first preset time length is 0.5-3 hours; the second preset time length is 0.5-2 hours.

Citation Information

Patent Citations

  • Hybrid nano-reinforced toughening agent for improving mechanical properties of cementing cement stones

    CN108485621A

  • High-oil-absorptivity resin and preparation method thereof

    CN110052250A

  • Additive for inhibiting hydration of cement as well as preparation method and application of additive

    CN115073654A

Cited By

  • Preparation method of thickening agent for fracturing

    CN121609838A